Sosialisasi Etika Bisnis untuk Peningkatan Manajemen Usaha Pelaku UMKM Mekar Sari di Desa Kore - Muhammad Yusuf; Sulistyo Utami; Ira Fauziah; Dina Febriyanti (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
Doing business, big or small, is bound up with ethical issues. Ethics refers to what a person should do morally. PKM activity partners are UKMs engaged in the field of making snack products made from cashew nuts, located in Kore Village, Sanggar District, Bima Regency. PKM activities aim to provide partners with knowledge about business ethics that partners need to have in doing business. Plus, partner businesses are located in densely populated areas. It is necessary to maintain ethical behavior where the partner's business is located. The method offered to partners/MSMEs is education/socialization using LEAFLET which is carried out door to door. The material provided in the leaflet includes a discussion of (1) The role of ethics in business for MSMEs, (2) Benefits of doing business for MSMEs (3) Application of ethical principles in business in financial, marketing, production and HR activities. The results of the activity showed that partners were very enthusiastic in listening and discussing during the activity. Apart from that, it can provide knowledge about ethics in running a business.